PERAWATAN GIGI SUPERNUMERARY RAHANG ATAS PADA MASA GIGI BERCAMPUR: LAPORAN KASUS - Hilda Fitria Lubis (Journal of Syiah Kuala Dentistry Society, 2016)
AbstractSupernumerary teeth is one of the etiology of crowding and a serious problem for patients because it can be a risk factor supernumerary tooth malocclusion especially if it grows in the anterior part between the two incisor teeth ( mesiodens ) so that patients feel uncomfortable which can result in disturbing appearance . The etiology of supernumerary teeth from heriditer factor , disruptions / anomalies growth of teeth and other tissues as well as some theory that suggests the etiology such as avatisme theory and the theory of dichotomy . Male patients aged 9 years came to the Department of Orthodontics RSGMP FKG USU with complaints of upper anterior teeth crowding . Changes in treatment results obtained within 4 months using removable orthodontic device is active . Early treatment in this case is recommended due to prevent malocclusion become more severe . This tool is easy to make, efficient and well tolerated by patients .